Integrating Emerging Sports into Primary Physical Education: A Four-Dimensional Curriculum Framework for Holistic Student Development in China - Li, meng (Pacific International Journal, 2025)
In response to the ongoing educational reform and the global movement toward diversified physical education, this study explores effective strategies for integrating emerging sports into primary school physical education (PE) curricula in China. Using literature analysis, teaching experiments, and comparative research, the study examines the application of rope skipping, roller skating, and orienteering as innovative modules in PE instruction. A four-dimensional integration framework—comprising progressive skill reconstruction, spiral physical fitness enhancement, interactive and interest-oriented pedagogy, and multi-dimensional evaluation—was developed and tested in teaching practice. Results indicate that curriculum integration of emerging sports significantly improves students’ motor skills, physical fitness, and learning motivation while promoting teamwork and self-efficacy. The study concludes that effective integration should adhere to the principles of scientific design, enjoyment, and practicality, using gamification, situational learning, and competition-based instruction. This framework offers a new pathway for promoting holistic physical literacy and health-oriented development among primary school students.